A comprehensive review on day‐ahead electricity market and important features of world's major electric power exchanges. (1st March 2020) - Shah, Devnath; Chatterjee, Saibal
Summary: Restructuring to the existing electric power system has transformed the conventional method in which electric power is traded around the globe. Now private players and entities having distributed generators can actively participate in restructured electricity market. It brings competition among different market players and leads to an overall fall in electricity prices. To further enhance competitiveness and bring transparency in the electric power trading mechanism, a common platform called power exchange (PX) has been established in many countries of the world. PX is a common internet‐based online platform where various market players submit their offers/bids for selling/buying electrical energy or services. As in today's restructured electricity market, significant percentage of short‐term electric power is traded through day‐ahead market (DAM) of PX, the study of DAM is very important. Therefore, this article presents a comprehensive review of day‐ahead electricity market and other important features of world's major electric power exchanges. It mainly focused on PX products, trading mechanism, DAM design issues, world's major PX, comparative analysis of DAM of world's major PX and future challenges.